Analisis Diklat Terhadap Kinerja Pegawai Dinas Komunikasi dan Informatika Kabuoaten Kubu Raya - Marissa B31106068, Anggi (Jurnal Manajemen Update, 2014)
This study about ï¿½Analysis of Relationship Between Education and Experience to Employee Performance on dinas Komunikasi dan Informatika Kabuoaten Kubu. This study aims to know the description of education and working experience to employee performance on Komunikasi dan Informatika Kabuoaten Kubu.The form of research used in this study are descriptive study and causality, with survey methods and data collection techniques are primary and secondary data. Sampling conducted using saturated sampling or census with 33 samples as respondents which was all of the employee on Komunikasi dan Informatika Kabuoaten Kubu. So the data that used is population data. Data analysis technique that used are descriptive analysis and regression analysis with using multiple regression to analyze the relationship between independent variable that is education and experience to dependent variable that is performance.The result of research concluded that the partial test or t-test, find that education and experience significant effect to employees performance on Komunikasi dan Informatika Kabuoaten Kubu. Simultaneously testing or f-test, find that both of education and experience have significant effect to employees performance on Komunikasi dan Informatika Kabuoaten Kubu.